The Urgency Of Applying The Principle Of "Debt Forgiveness" For Individual Debtors Of Msme Owners In The Bankruptcy Process - Ayyza Rachma Zahranisza; Iwan Erar Joesoef (PALAR | PAKUAN LAW REVIEW, 2026)
Individual debtors, especially MSME owners, are often trapped in bankruptcy situations that cannot be resolved due to insufficient assets to pay outstanding debts to creditors. Substantially, this debt burden persistently shackles individual debtors. Damage to their financial reputation, coupled with the possibility of future lawsuits, significantly limits their ability to regain a decent economic life after the bankruptcy process is completed. The purpose of this study is to analyze the urgency of applying the principle of “debt forgiveness” that can provide justice for debtors and creditors in the bankruptcy process, especially for individual debtors who own MSMEs. The research method used is normative juridical with a case approach and a regulatory approach using secondary data sources. The results of the study indicate that in order to achieve a balance between debtors and creditors, needs to be a mechanism for applying the principle of “debt forgiveness” that provides relief for debtors to be able to write off all or part of their remaining debt, which can be proven by good faith and the limited financial capacity of debtors who have remaining debt from the failure of their MSME. This will provide debtors with the opportunity to rebuild their economic lives without constantly being overshadowed by the demands of past outstanding debts. Keywords: The Principle of “Debt Forgiveness”, Individual Debtors, MSME Owners, Bankruptcy.